2008
DOI: 10.3923/pjbs.2008.1380.1384
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Using Insecticidal Properties of Medicinal Plants Against Insect Pests

Abstract: In this study, botanicals extracted from two the species of family Scrophulariaceae, Verbascum cheiranthifolium Boiss and Verbascum speciosum Schard, were examined for their effect on mortality and progeny production against adults of Sitophilus oryzae (L.). The plant extracts were applied at five dose rates, which 0.25, 0.5, 1.0, 2.0 and 3% (w/v). Adults of S. oryzae was exposed to the treated wheat at 25 degrees C and 65% RH and mortality was assessed after 24 h, 48 h, 7 day, 14 day and 21 day of exposure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…The present results in this study was showed that the botanical extracts were effective aganist S. oryzae but its effectiveness was highly determined by the concentration rate and exposure intervals .One of the most interesting findings of the current study was the dissimilar efficacy of botanical materials among plant species so that, S. melongena was more effective against S. oryzae on treated grains than C.rotundus. Moreover, results showed that for this insect concentration rates and longer exposures intervals were needed to obtain a satisfactory level of mortality rates However, the present result indicated that higher concentrations of these plant extracts for a relatively short period are much more effective than lower concentration for along period, similar observation on other plant extracts on several insects have been reported for example Khoshnoud et al (2008) showed that plant extracts of Verbascum cheiranifolium Boiss and Verbascum speciasum Schard possess toxic principles with significant insecticidal effect against S. oryzae Repellency test.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The present results in this study was showed that the botanical extracts were effective aganist S. oryzae but its effectiveness was highly determined by the concentration rate and exposure intervals .One of the most interesting findings of the current study was the dissimilar efficacy of botanical materials among plant species so that, S. melongena was more effective against S. oryzae on treated grains than C.rotundus. Moreover, results showed that for this insect concentration rates and longer exposures intervals were needed to obtain a satisfactory level of mortality rates However, the present result indicated that higher concentrations of these plant extracts for a relatively short period are much more effective than lower concentration for along period, similar observation on other plant extracts on several insects have been reported for example Khoshnoud et al (2008) showed that plant extracts of Verbascum cheiranifolium Boiss and Verbascum speciasum Schard possess toxic principles with significant insecticidal effect against S. oryzae Repellency test.…”
Section: Resultssupporting
confidence: 80%
“…These results agree with (Yanckanchi and Gadach 2010) when they used ethanol extracts of Withonta somnifera L. (Solanacae), they found the mortality rates were increased with increasing the concentration of plant extracts and exposure time. This conclusion was also confirmed by (Khoshnoud et al, 2008) and (Gupta and Srivastava, 2008). From Fig.1 it is obvious that plant extract of S. melongena was more effective against S. oryzae than C. rotundus .Where the rice grains weevils treated with acetone extracts of S.melongena and C. rotundus produced higher mortality rate at high concentration with (LC 50 ) was14.23 and 54.69, respectively, after 17 days.…”
Section: Resultssupporting
confidence: 64%
“…The findings obtained in this study agreed with the earlier reports that plant extracts could adequately protect stored wheat from attack of its major insect pest of R. dominica owing to its F1 progeny production significant suppression. The ability of a botanical to act as biopesticides is not only accessed by its ability to evoked adult mortality but by its capability to hinder offspring development in treated grains (Khoshnoud et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Now we know that the use of synthetic insecticides may lead to several problems such as toxicity in humans, cattle and pets including groundwater contamination, disruption of natural biological control, destruction of wildlife, and the parasite's development of resistance to pesticides (Marco et al 1986; Van Der Hoek 1998; Isman 2006). Therefore, many researchers are interested in using botanical insecticides instead for protection against insects in stored products (Isman 2006; Khoshnoud et al 2008) or as mosquito repellents (Müller et al 2009; Carroll and Loye 2006). But the historical use of plant-based repellents for protection against domestic parasites has been underestimated to date.…”
Section: Introductionmentioning
confidence: 99%